Carbon Border Adjustment Mechanism: Between Climate Target and Climate Justice - Ula, Hikmatul (Universitas Brawijaya, 2026)
The Carbon Border Adjustment Mechanism (CBAM) raises urgent legal questions about whether climate ambition pursued through border measures can be reconciled with equity and common but differentiated responsibilities and respective capabilities (CBDR-RC), and sustainable development. While Mehling et al. (2019) examine border carbon adjustments as tools for enhanced climate action and trade-law legitimacy, Beaufils et al. (2023) assess their distributional impacts on trade partners, and Boute (2024) analyses the recognition of third-country carbon pricing, these studies remain insufficiently integrated in explaining CBAM simultaneously as a climate-target instrument and a justice-sensitive legal mechanism. This article aims to critically assess whether CBAM can prevent carbon leakage and extend carbon pricing to imports without imposing disproportionate transition burdens on developing countries and carbon-intensive exporters. It employs normative legal research using statutory, conceptual, and critical policy approaches, focusing on Regulation (EU) 2023/956, international climate law, WTO-related principles, and climate justice scholarship. The article finds that CBAM may strengthen carbon accountability and protect the integrity of EU climate policy, but its current design remains overly centred on carbon-cost equalisation and gives inadequate recognition to differentiated capacities, non-price climate policies, procedural participation, and revenue equity. It concludes that CBAM should move from equal carbon pricing toward equitable carbon-cost differentiation. The article recommends differentiated compliance pathways, recognition of diverse mitigation measures, technical assistance, and revenue recycling for affected developing countries. Its contribution lies in offering foreign readers a critical legal framework for evaluating CBAM beyond EU competitiveness, as a test of fairness in global climate-trade governance.